2017
DOI: 10.1016/j.kint.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide overexpression ameliorates hepatorenal fibrocystic disease in a rat model of polycystic kidney disease

Abstract: Polycystic kidney disease (PKD) involves progressive hepatorenal cyst expansion and fibrosis, frequently leading to end-stage renal disease. Increased vasopressin and cAMP signaling, dysregulated calcium homeostasis, and hypertension play major roles in PKD progression. The guanylyl cyclase A agonist, B-type natriuretic peptide (BNP), stimulates cGMP and shows anti-fibrotic, anti-hypertensive, and vasopressin-suppressive effects, potentially counteracting PKD pathogenesis. Here, we assessed the impacts of guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Conversely, reduced renal corin expression has been reported in rat kidney disease models [ 36 , 72 ] and in patients with chronic kidney disease and sodium retention [ 41 ]. In previous studies in animal models and patients, altered natriuretic peptide expression and processing have been found as mechanisms underlying hypertension and cardiorenal disease [ 73 , 74 , 75 , 76 , 77 ]. In a recent study, altered corin expression in the heart was also found in patients with chronic kidney disease [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, reduced renal corin expression has been reported in rat kidney disease models [ 36 , 72 ] and in patients with chronic kidney disease and sodium retention [ 41 ]. In previous studies in animal models and patients, altered natriuretic peptide expression and processing have been found as mechanisms underlying hypertension and cardiorenal disease [ 73 , 74 , 75 , 76 , 77 ]. In a recent study, altered corin expression in the heart was also found in patients with chronic kidney disease [ 78 ].…”
Section: Discussionmentioning
confidence: 99%